Information System Audit on the Catatmak Application on the Web and Playstore Using the Cobit Framework for Financial Recording : Study Case : Application Note - Fariz Nur Fikri Zaki; Putri Awaliatuz Zahra; Vidia Alma Cyrilla; Wahyu Latifatun; Jeffri Prayitno Bangkit Saputra (International Journal of Information Engineering and Science, 2025)
PT Jadi Kaya Raya Bersama, founded in 2024 in Banyumas, Indonesia, focuses on providing reliable financial recording solutions for Micro, Small, and Medium Enterprises (MSMEs) through fintech-based applications. The platform is designed to support transaction recording, financial monitoring, and reporting processes to improve MSME financial management. Despite its significant potential, several technical issues have hindered the application’s performance and service quality. Key problems identified include disruptions in the WhatsApp Bot API, user authentication errors, and the lack of integration with banking systems and digital wallet services. These challenges affect transaction recording accuracy, operational efficiency, and the security of user financial data. To identify the root causes of these issues and propose appropriate solutions, a system audit was conducted using the COBIT framework as a governance and management evaluation tool. The audit process involved assessing system performance, control mechanisms, and IT service management practices. The results indicate that API disruptions were primarily caused by network instability and configuration errors, which led to interruptions in automated transaction recording services. Meanwhile, authentication problems were associated with weak login mechanisms and insufficient identity verification processes. In addition, the application’s inability to integrate with banking and e-money services created limitations in transaction synchronization and reduced overall user convenience. Based on these findings, several strategic recommendations are proposed. These include optimizing API performance, strengthening authentication systems through the implementation of Two-Factor Authentication (2FA), and developing integration capabilities with banking institutions and digital wallet platforms. The implementation of these improvements is expected to enhance system efficiency, data security, and service quality. Ultimately, strengthening the fintech application’s performance will support MSMEs financial management and contribute to sustainable digital economic growth in Indonesia.